PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAH BERBASIS AKRUAL, SISTEM INFORMASI AKUNTANSI DINAS DAERAH, DAN GOOD PUBLIC GOVERNANCE TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH: (Studi pada SKPD dan OPD Kabupaten Sleman) - Herinda, Dorotea Yovita Putri; Sulistiyowati, Firma (Jurnal Manajemen dan Bisnis, 2023)
The purpose of this research is to examine the role of government accounting standards based on approach, accounting information system of the regional agency, and good public governance implementation on the quality of local government financial report Sleman District. This method used in this research was the quantitative method with a survey approach. The sample collection in this research uses total of sampling technique. The instrument used in this research is a question with four points Likert scale. The data analysis technique used in this research is validity test using Pearson Product Moment correlation, reliability test using Cronbach’s Alpha, assumption classic test using normality, multicollinearity, and heteroscedasticity test. The hypothesis was tested using multiple regression analysis. The result of multiple regression analysis shows that government accounting standards based on accrual approach, accounting information system of the regional agency, and good public governance implementation were positive significantly affected by the quality of local government financial report of Sleman District.